An International Study of the Contextual Effects of Gender Inequality on Intimate Partner Sexual Violence Against Women Students. (January 2020) - LeSuer, Will
Rejecting biological and essentialist explanations, feminist scholars posit that gender inequality is a driving force behind sexual violence against women. Using an ecological approach, I test for significant associations between national-level gender inequality and intimate partner sexual violence (IPSV). I use multi-level generalized linear modeling to analyze the responses of 9, 126 women from 29 countries in the International Dating Violence Study. I find that while controlling for other risk factors, gender inequality is significantly associated with increased odds of having experienced severe, but not minor, forms of IPSV.